169k views
2 votes
Please show me how to factor X⁴ - 1 =

Please show the steps. thank you very much, Jim

User Fatouma
by
4.7k points

1 Answer

4 votes

Answer:

factoring the term
x^4-1 we get
\mathbf{(x^2+1)(x-1)(x+1}

Explanation:

We need to factor the term
x^4-1

We know that
a^2-b^2=(a-b)(a+b)

We can write
x^4 \ as \ (x^2)^2

Simplifying:


x^4-1\\=(x^2)^2-1\\=(x^2-1)(x^2+1)\\

Now, again using formula
a^2-b^2=(a-b)(a+b)


=(x^2+1)((x)^2-1)\\=(x^2+1)(x-1)(x+1)

So, factoring the term
x^4-1 we get
\mathbf{(x^2+1)(x-1)(x+1}

User Paul Adamson
by
4.7k points